2019
DOI: 10.3389/fgene.2019.01142
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Genes and Functionally Enriched Pathways in Sjögren’s Syndrome by Weighted Gene Co-Expression Network Analysis

Abstract: Purpose: Sjögren’s syndrome (SS) is an autoimmune disease characterized by dry mouth and eyes. To date, the exact molecular mechanisms of its etiology are still largely unknown. The aim of this study was to identify SS related key genes and functionally enriched pathways using the weighted gene co-expression network analysis (WGCNA).Materials and Methods: We downloaded the microarray data of 190 SS patients and 32 controls from Gene Expression Omnibus (GEO). Gene network was constructed and genes were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 35 publications
2
54
2
Order By: Relevance
“…In addition, WGCNA has been applied to construct gene co-expression network modules and identify hub genes in several autoimmune diseases, including rheumatoid arthritis (RA) (Ma et al, 2017), inflammatory bowel disease (IBD) (Li et al, 2016), and autoimmune thyroid disease (ATD) (Shao et al, 2018). Moreover, the gene expression profiles of more than 200 PBMC samples of pSS have been investigated, and WGCNA analysis was applied to explore the gene-network signature and potential functions of hub genes based on Gene Expression Omnibus (GEO) public database (Yao et al, 2019). Recently, Inamo et al (2020) also identified LINC00487 and SOX4 as key genes associated with the dysregulation of B cells in pSS patients using WGCNA algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WGCNA has been applied to construct gene co-expression network modules and identify hub genes in several autoimmune diseases, including rheumatoid arthritis (RA) (Ma et al, 2017), inflammatory bowel disease (IBD) (Li et al, 2016), and autoimmune thyroid disease (ATD) (Shao et al, 2018). Moreover, the gene expression profiles of more than 200 PBMC samples of pSS have been investigated, and WGCNA analysis was applied to explore the gene-network signature and potential functions of hub genes based on Gene Expression Omnibus (GEO) public database (Yao et al, 2019). Recently, Inamo et al (2020) also identified LINC00487 and SOX4 as key genes associated with the dysregulation of B cells in pSS patients using WGCNA algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Type I IFN may therefore inhibit XIAP function by the induction of XAF1, and then negatively regulate the inhibitor of apoptosis. XAF1 was upregulated in whole peripheral blood from the Sjögren's syndrome patients compared with controls [46]. However, there have been no research about the role of XAF1 in SLE/LN progression.…”
Section: Discussionmentioning
confidence: 90%
“…Most immune cell types express cytosolic RNA-sensing receptors and their downstream signaling molecules at steady state [ 112 ]. Considering that the RNA-sensing receptors themselves are IFN-regulated, it is not surprising to see increased gene expression of IFIH1/MDA5 , DDX58/RIG-I , EIF2AK2/PKR, and OAS in whole blood and specific leukocyte subsets from pSS patients [ 62 , 64 , 66 , 118 , 119 , 120 , 121 ]. Studies detecting active signaling and functional properties of these pathways in pSS cells have been very limited so far.…”
Section: Cytosolic Ifn-inducing Rna-sensing Pathways In Primary Sjmentioning
confidence: 99%